1996
DOI: 10.1080/00986449608936652
|View full text |Cite
|
Sign up to set email alerts
|

The Slow Motion of a Spherical Particle in a Carreau Fluid

Abstract: The drag on a spherical particle is studied for two limiting cases, namely for the rigid sphere and for the bubble, An approximate solution is found for creeping flow around a particle suspended in a shearthinning fluid, The three parameter Carreau model is used to represent the suspending liquid, The drag force on the particle for both cases is calculated by a perturbation method around the Newtonian solution in the limit or small Carreaunumber. The resultingexpressions arc found to be dependenton the Carreau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…This conclusion is consistent with that of Mena et al [13]. Rodrigue et al [14] investigated analytically the movement of a spherical bubble and a rigid particle in an infinite Carreau fluid under conditions of creeping flow. Shahcheraghi and Dwyer [15] analyzed the problem of the flow of an incompressible Newtonian fluid over a spherical object placed in a pipe under the condition of convective flow, taking the effect of heat transfer into account.…”
Section: Introductionsupporting
confidence: 88%
“…This conclusion is consistent with that of Mena et al [13]. Rodrigue et al [14] investigated analytically the movement of a spherical bubble and a rigid particle in an infinite Carreau fluid under conditions of creeping flow. Shahcheraghi and Dwyer [15] analyzed the problem of the flow of an incompressible Newtonian fluid over a spherical object placed in a pipe under the condition of convective flow, taking the effect of heat transfer into account.…”
Section: Introductionsupporting
confidence: 88%
“…We will follow the development of Rodrigue et al (1996) where the fluid is described by the three parameter Carreau model in the limit of small Carreau number using a perturbation method. The Carreau model is given by:…”
Section: Resultsmentioning
confidence: 99%
“…For sedimentation in a non-Newtonian fluid, almost all of the available results are limited to spherical particles [2][3][4][5] and that for nonspherical particles are relatively limited [6][7][8][9][10][11]. Several attempts were made concerning the sedimentation in a viscoelastic fluid, and behaviors that are different from those in a Newtonian fluid were observed (e.g., [12][13][14][15][16]). The sedimentation of particles in a shear-thinning fluid has also been studied by many investigators.…”
Section: Introductionmentioning
confidence: 99%
“…The sedimentation of particles in a shear-thinning fluid has also been studied by many investigators. Under the creeping flow condition, Rodrigue et al [16] derived the drag coefficients of both rigid spheres and bubbles in an infinite Carreau fluid. It was shown that the influence of the shear-thinning nature of a Carreau fluid on a rigid sphere is greater than that on a bubble.…”
Section: Introductionmentioning
confidence: 99%